Factors Affecting Health Service Utilization for Chronic Conditions: A Bibliometric Review of Primary Health Care - Sanni Rizky Putri; M. Bakhriansyah; Husaini Husaini; Musafaah Musafaah; Izaak Zoelkarnain (Universitas Malahayati Lampung, 2024)
ABSTRACT Non-communicable diseases (NCDs) such as heart disease, diabetes and cancer are significant global health challenges, particularly in developing countries. Understanding healthcare utilization for NCDs is critical to improving healthcare outcomes and patient quality of life. This study aims to analyze trends and identify research gaps in healthcare utilization for NCDs through bibliometric analysis. With this approach, this study seeks to provide a comprehensive overview of research developments in this field and identify areas that require further attention. This study used bibliometric analysis with the Publish or Perish app and a Google Scholar search using the keywords